Teachers' and Students' Perceptions of the Arabic Language E-Learning Platform - Musonif, Mohammad Zaelani; Mahliatussikah, Hanik; Ismail, Zawawi (Institut Agama Islam Negeri Curup, 2023)
This study aims to analyze and describe teachers’ and students’ perceptions about E-learning used in Minhah's class at the Markaz Arabiyah Arabic course institution. Technological progress is necessary and affects all aspects of life, including education. The influence of technological advancement can be found in the emergence of e-learning as an interactive learning media innovation that can be utilized in realizing active, innovative and independent learning and not only supporting students in mastering materials but also accelerating students in mastering 21st-century learning competencies. E-learning is becoming the right choice to realize effective distance learning. The method used in this research was a survey research method with a quantitative approach. Data were collected using observation techniques, questionnaires, and literature studies. The results showed that the Markaz Arabiyah e-learning used in learning at the Minhah Mesir Program was categorized as good in the visual aspect and quite good in the media engineering aspect, with an average percentage for the visual aspect of 79.2% and for the media engineering aspect of 71%. These results indicated that e-learning had a good appearance and features adjusted to progress technology and students' needs in accessing practice questions. However, regarding content and material aspects, Markaz Arabiyah was in a bad category with an average percentage score of 44% each. The category was not good for both indicators because the Markaz Arabiyah e-learning did not yet contain material and was only used as a learning evaluation media.